How Social Capital Works: The Role of Social Capital in Acts of Corruption - Nadjib, Abdul; Madri Bafadhal, Oemar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to provide an alternative perspective on seeing corruption in Indonesia. In addition to individual and organizational factors of psychological, technical, and systemic aspects that have been massively discussed, cultural aspects such as social capital also contribute to corrupt behaviors, particularly at the local level. We use a critical perspective to enrich the analysis of corruption in relation to and with social capital. This research found that corruption occurs because of clientelism habitus, which encourages people to user their social capital in order to get the desired feedback. Clientelism habitus also prevents some people from accessing social capital. It is related to the common practice of corruption in Indonesia, which is bribery. The practical implication of this study is that social capital needs to be well distributed by performing political reform movements that can connect people’s access to an arena so as to increase the capital they have. When everyone has the same social capital, access to other capital can be opened so that it can minimize corrupt behavior.